Factors Associated with The Motivation of Palm Sugar Producers in Malapari Village Muara Bulian Batanghari Regency - Rosyani, Rosyani; Sativa, Fendria; Adinda Nugraha, Naila (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
This study aims to describe the factors associated with the motivation of palm sugar producers in Malapari Village, Muara Bulian Sub-district, Batanghari Regency; to describe the motivation of palm sugar producers in Malapari Village, Muara Bulian Sub-district, Batanghari Regency; and to analyze the factors associated with the motivation of palm sugar producers in Malapari Village, Muara Bulian Sub-district, Batanghari Regency. This research was conducted in Malapari Village, Muara Bulian Sub-district, Batanghari Regency. This area was selected based on the consideration that Malapari Village is the center for palm sugar production in Batanghari. The collected data were analyzed using non-parametric statistics through the Chi-Square test. The results obtained from the study are: 1) The factors associated with the producer’s motivation tend to be high, with the following percentages: education factor 58%, experience factor 65%, raw material availability factor 58.3%, tradition factor 53%, sales factor 78%, and government policy factor 63%. 2) The motivation of palm sugar producer in Malapari Village tends to be high, with the following percentages for its aspects: Existence 80%, Relatedness 76.6%, and Growth 90%. The overall aspect of motivation is 75%. 3) Based on the Chi-Square analysis results, there is a significant relationship between the factors and the motivation of palm sugar producer in Malapari Village, Muara Bulian Sub-district, Batanghari Regency at the 95% significance level.